Spiritual development in executive coaching. Issue 10 (11th November 2019) - Allen, Stuart; Fry, Louis W.
Abstract : Purpose: Spiritual topics emerge in executive leadership coaching. However, the scholarly literature has emphasized the performance development aspects of executive coaching (EC) more than the development of executives' inner lives, although there is some evidence of practitioners addressing spiritual topics. Executive leaders have spiritual needs and executive coaches may be well positioned to address the intersection of the leaders' work and spiritual lives, provided coaches observe skill boundaries and the limitations of the coaching context. The purpose of this paper is to discuss the merits of including spiritual development (SDev) in EC and how executive coaches can incorporate it in their practice. Design/methodology/approach: EC, SDev and spiritual direction are compared, drawing attention to conflicting and complementary aspects of SDev applied in EC. Organizations', clients' and coaches' likely concerns about such integration are explored and addressed. Suitable contexts, principles, a basic developmental framework and practical steps for executive coaches considering the inclusion of SDev in EC are proposed. Findings: The paper provides coaches, consultants, executives and those charged with executive development with a foundational understanding of the role of SDev in EC. Originality/value: A framework is provided for professionals involved in executive management development to address executive leaders' spiritual needs through EC.